Studi Pemetaan Kerawanan Gempabumi Berdasarkan Pola-Pola Sesar Menggunakan Focal Mechanism dari Data Gempabumi di Wilayah Bali - Maria Crisanti Uduk; I Ketut Sukarasa; Arief Tyastama; Komang Ngurah Suarbawa; Nyoman Wendri; I Nengah Sandi (Kappa Journal, 2025)
Research regarding earthquake vulnerability mapping studies based on fault patterns using focal mechanism data from earthquake data in the Bali Region has been carried out. This research aims to determine fault patterns in the Bali region using a focal mechanism from earthquake data for 1976-2021, determine the types of faults in the Bali region when analyzed using the focal mechanism method and determine areas that are prone to earthquakes in the Bali region. The data used are seismograph recordings obtained from the Global Centroid Moment Tensor (CMT) and the United States Geological Survey (USGS). The method used in this research is the focal mechanism method. The results of mapping the distribution of focal balls in the Bali region are that there were 9 earthquake events above 4 M, with 8 events being thrust faults and 1 being an oblique fault. Areas that are prone to earthquakes are in the East Bali region, specifically in Karangasam, and in general earthquakes occur in water areas or at sea. The results of the seismicity map of the distribution of earthquakes show that the depth of earthquakes in the Bali region varies. On the seismicity map, it can be seen that the most dominant ones are earthquakes in the deep and medium earthquake categories, but the most dangerous are earthquakes in the shallow depth category.